Nature and features methodically preparing future teachers to work in innovative processes in school social science education (Pedagogy of Higher and Secondary Education, 2013)
Nikora A. Nature and features methodically preparing future teachers to work in innovative processes in school social science education.Article is devoted to the definition of the nature and characteristics of the disclosure of methodological training future teachers to work in terms of innovation processes in the school social science education.
Keywords: methodical teacher training; innovative process; social science education